Fenomena Penggunaan Bahasa Arab oleh Masyarakat Keturunan Arab di “Embong Arab” Malang - Afif Kholisun Nashoih; Hilyah Ashoumi (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2018)
This study aims to describe the pattern of use of Arabic by the Arab community in the embong Arab, as well as variations and selection of language codes in their communication. Through a sociolinguistic approach, this descriptive study uses two methods, see and competent, to collect data in the form of speech from Arab descendants in embong Arab Malang, then analyze it using the extralingual equivalent method. Based on the results of the study, it was found that the Arabic language experienced rapid development due to language contact, which caused interference which resulted in deviations from the standard Arabic rules or fushah. The use of Arabic by the embong Arab community is not monolithic, because Indonesian and Javanese languages ??are also a variation of their language, resulting in mixed code events and code switching as a strategy for using Arabic. Although it is not uncommon to find a single use of language, both Arabic fushah and amiyah, Indonesian, and Javanese Ngoko. Each language variation is used according to the speech situation, speech partners, and speech goals